Physiological dynamics as indicators of plant response to manganese binary effect - Zhenggang, Xu; Li, Fan; Mengxi, Zheng; Yunlin, Zhao; Huimin, Huang; Guiyan, Yang (Frontiers in Plant Science, 2023)
Heavy metals negatively affect plant physiology. However, plants can reduce their toxicity through physiological responses. Broussonetia papyrifera is a suitable candidate tree for carrying out the phytoremediation of manganese (Mn)-contaminated soil. Considering Mn stress typically exerts a binary effect on plants, to reveal the dynamic characteristics of physiological indexes of B. papyrifera to Mn stress, we conducted pot experiments with six different Mn concentrations (0, 0.25, 0.5, 1, 2, and 5 mmol/L) for 60 days. In addition to the chlorophyll content, malondialdehyde (MDA), proline (PRO), soluble sugar, superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), the absorption and transfer characteristics of Mn, and root structure were also measured. Phytoremedial potential parameters such as the bioconcentration factor (BCF) and translocation factor (TF) displayed an increasing trend with the increase of Mn concentration. At the lower Mn concentrations (<0.5 mmol/L), TF value was <1, but crossed 1 when the Mn concentration exceeded 100 mmol/L. The Mn distribution in various tissues was in the following order: leaf > stem > root. The root structure analysis revealed that low-level concentrations of Mn (1 mmol/L) promoted the root development. Mn concentration and stress duration had significant effects on all measured physiological indexes and except soluble sugar, Mn concentration and stress time displayed a significant interaction on the physiological indexes. Our study demonstrates that the physiological indexes of B. papyrifera display dynamic characteristics under Mn stress. Thus, during the monitoring process of Mn stress, it appears to be necessary to appropriately select sampling parts according to Mn concentration.